Handling Crimes of Violence Against Women and Children by the PPA Unit of Blitar Police Satreskrim - Damayanti, Shafa Fitrisya Kharisma (Advances in Police Science Research Journal, 2024)
Cases of violence against women and children are rampant in various regions and need direct law enforcement, as is the case in the jurisdiction of Blitar Police. The purpose of this study is to describe the organisational resources of the PPA Unit of Satreskrim at Blitar Police and describe the management stages in handling criminal acts of violence against women and children. The approach in this research was descriptive qualitative, with the type of field research. The research data used are two types of data, namely primary data derived from observations and interviews, while secondary data comes from related documents. Data validity used is triangulation of sources, techniques, and theories. The data analysis method uses data reduction techniques, data presentation, and conclusion drawing. The findings show that the PPA Unit of Blitar Police still experiences obstacles in terms of managing its organisational resources, as seen from the limited number and quality of its human resources. POAC analysis shows that planning, organizing, actuating dan controlling efforts are not yet fully optimal.